2004
DOI: 10.1073/pnas.0305363101
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutations of the juxtamembrane tyrosines in the Kit receptor tyrosine kinase selectively affect multiple cell lineages

Abstract: Loss-of-function mutations in the murine dominant white spotting ͞c-kit locus affect a diverse array of biological processes and cell lineages and cause a range of phenotypes, including severe anemia, defective pigmentation, sterility, mast cell deficits, a lack of interstitial cells of Cajal, spatial learning memory deficits, and defects in peripheral nerve regeneration. Here we show that tyrosine residues 567 and 569 in the juxtamembrane (Jx) domain of the murine Kit receptor tyrosine kinase are crucial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 56 publications
1
67
0
Order By: Relevance
“…8). Two recent papers showed that there are Ͼ95% deceases of mast cells in the peritoneal cavity (6,43) and stomach (43) of Kit Y567F knock-in mice. The loss of mast cells in these two tissues in the Kit Y567F/Y567F mice resembles the phenotypes that were observed in Gab2 Ϫ/Ϫ mice (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8). Two recent papers showed that there are Ͼ95% deceases of mast cells in the peritoneal cavity (6,43) and stomach (43) of Kit Y567F knock-in mice. The loss of mast cells in these two tissues in the Kit Y567F/Y567F mice resembles the phenotypes that were observed in Gab2 Ϫ/Ϫ mice (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of mast cells in hypodermis (Fig. 7B), stomach (32), and peritoneal cavity (6,30,32,43) (data not shown) suggest that the Kit Tyr 567 -Gab2 activated pathway is more important than the Kit Tyr 719 pathway in mast cell development in these specific tissues. One possibility is that the signal from Kit Tyr 719 might be transient or weak.…”
Section: Gab2/shp-2 Activates the Rac/jnk Pathway In Kit Signalingmentioning
confidence: 99%
“…5,7,8 Mutational and "knock-in" studies on Kit Y567/Y569 have revealed their important role in cell development, proliferation, survival, and migration. 6,[9][10][11] However, the biologic significance of these interactions is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies using knock-in mutations of individual KIT tyrosine residues identified key signaling pathways required for mast cell development (1,24,25,45,48). Phosphorylation of KIT Y719 allows recruitment of the p85␣ regulatory subunit of class I A phosphatidylinositol 3-kinase (PI3K) (44).…”
mentioning
confidence: 99%